Kartogenin preconditioning commits mesenchymal stem cells to a precartilaginous stage with enhanced chondrogenic potential by modulating JNK and β‐catenin–related pathways. Issue 4 (29th January 2019) - Jing, Hui; Zhang, Xiaoyang; Gao, Manchen; Luo, Kai; Fu, Wei; Yin, Meng; Wang, Wei; Zhu, Zhongqun; Zheng, Jinghao; He, Xiaomin
ABSTRACT: Cartilage engineering strategies using mesenchymal stem cells (MSCs) could provide preferable solutions to resolve long‐segment tracheal defects. However, the drawbacks of widely used chondrogenic protocols containing TGF‐β3, such as inefficiency and unstable cellular phenotype, are problematic. In our research, to optimize the chondrogenic differentiation of human umbilical cord MSCs (hUCMSCs), kartogenin (KGN) preconditioning was performed prior to TGF‐β3 induction. hUCMSCs were preconditioned with 1 µM of KGN for 3 d, sequentially pelleted, and incubated with TGF‐β3 for 28 d. Then, the expression of chondrogenesis‐ and ossification‐related genes was evaluated by immunohistochemistry and RT‐PCR. The underlying mechanism governing the beneficial effects of KGN preconditioning was explored by phosphorylated kinase screening and validated in vitro and in vivo using JNK inhibitor (SP600125) and β‐catenin activator (SKL2001). After KGN preconditioning, expression of fibroblast growth factor receptor 3, a marker of precartilaginous stem cells, was up‐regulated in hUCMSCs. Furthermore, the KGN‐preconditioned hUCMSCs efficiently differentiated into chondrocytes with elevated chondrogenic gene (SOX9, aggrecan, and collagen II) expression and reduced expression of ossifie genes (collagen X and MMP13 ) compared with hUCMSCs treated with TGF‐β3 only. Phosphokinase screening indicated that the beneficial effects of KGN preconditioning are directly related to an up‐regulation of JNK phosphorylation and a suppression of β‐catenin levels. Blocking and activating tests revealed that the prochondrogenic effects of KGN preconditioning was achieved mainly by activating the JNK/Runt‐related transcription factor (RUNX)1 pathway, and antiossific effects were imparted by suppressing the β‐catenin/RUNX2 pathway. Eventually, tracheal patches, based on KGN‐preconditioned hUCMSCs and TGF‐β3 encapsulated electrospun poly ( l ‐lactic acid‐co‐ε‐caprolactone)/collagen nanofilms, were successfully used for restoring tracheal defects in rabbit models. In summary, KGN preconditioning likely improves the chondrogenic differentiation of hUCMSCs by committing them to a precartilaginous stage with enhanced JNK phosphorylation and suppressed β‐catenin. This novel protocol consisting of KGN preconditioning and subsequent TGF‐β3 induction might be preferable for cartilage engineering strategies using MSCs.—Jing, H., Zhang, X., Gao, M., Luo, K., Fu, W., Yin, M., Wang, W., Zhu, Z., Zheng, J., He, X. Kartogenin preconditioning commits mesenchymal stem cells to a precartilaginous stage with enhanced chondrogenic potential by modulating JNK and β‐catenin—related pathways. FASEB J. 33, 5641–5653 (2019). www.fasebj.org